Idea vs. Icon: Two Competitions - Jeffrey Clark (Oz, 1986)
The United States is blessed with a natural landscape that is both expansive and richly varied. Our recent attitude toward the relationship between the built and natural environment, however, has been at best a naively romantic one and at worst an instrument of private exploitation...